PEMAPARAN APLIKASI KOMPUTER, MANAJEMEN KEUANGAN, DAN PERPAJAKAN DI SMK KOLESE TIARA BANGSA - Daris Purba; Riki; Putu Rani Susanthi; Yossi Hendriati; Puspita Rama Nopiana; Hazriyanto Hazriyanto; Nasruji Nasruji; Dadi Akhmad Perdana; Yuliadi Yuliadi; Rudi Yanto Batara Silalahi; Rina Rina; Suratman Suratman; V Ade Arianto CP; Asih Purwana Sari (ASOSIASI IDEBAHASA KEPRI, 2023)
This community service activity was carried out on students of SMK Kolese Tiara Bangsa Batam. The purpose of this service is to provide knowledge of mail-merge, financial management, and taxation to students. The devotion method is to use the counseling method for mail-merge material and the collaborative interactive lecture method for financial management and taxation material. Faculty and students are involved in this service. Service is carried out with 3 stages, namely the preparation stage, the implementation stage, and the evaluation stage. At the preparatory stage, observations are made to the object of devotion. At the implementation stage, the provision of bidding materials is carried out. At the evaluation stage, an assessment of the implementation of service is carried out. The results of the service show that students really need this material because they rarely get it in school except for taxation materials. The results of the evaluation show an increase in students' knowledge of the material presented. This service suggests that service activities should be carried out that are more devoted to the delivery of financial management materials.